2022
DOI: 10.5194/gmd-15-269-2022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of increased resolution on long-standing biases in HighResMIP-PRIMAVERA climate models

Abstract: Abstract. We examine the influence of increased resolution on four long-standing biases using five different climate models developed within the PRIMAVERA project. The biases are the warm eastern tropical oceans, the double Intertropical Convergence Zone (ITCZ), the warm Southern Ocean, and the cold North Atlantic. Atmosphere resolution increases from ∼100–200 to ∼25–50 km, and ocean resolution increases from ∼1∘ (eddy-parametrized) to ∼0.25∘ (eddy-present). For one model, ocean resolution also reaches 1/12∘ (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 121 publications
4
39
0
1
Order By: Relevance
“…The PRIMAVERA atmosphere-only simulations are forced by HadISST2.2.0.0 sea surface boundary conditions. 19 The PRIMAVERA atmosphere-only simulations provide an opportunity to decide whether performance issues arise from ocean-atmosphere coupling (Moreno-Chamarro et al 2022). PRIMAVERA coupled and atmosphere-only simulations use the same external radiative forcings, as described in the High-ResMIP protocol (Haarsma et al 2016).…”
Section: Primavera Gcmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PRIMAVERA atmosphere-only simulations are forced by HadISST2.2.0.0 sea surface boundary conditions. 19 The PRIMAVERA atmosphere-only simulations provide an opportunity to decide whether performance issues arise from ocean-atmosphere coupling (Moreno-Chamarro et al 2022). PRIMAVERA coupled and atmosphere-only simulations use the same external radiative forcings, as described in the High-ResMIP protocol (Haarsma et al 2016).…”
Section: Primavera Gcmsmentioning
confidence: 99%
“…As suggested by Graham et al (2004) and already shown by Cantalloube et al (2020), climate models that project scenarios of anthropogenic radiative forcing into the future may prove useful. To address particular topographic textures as they often appear at astronomical sites, GCMs with the highest possible horizontal resolution are advantageous (Moreno-Chamarro et al 2022). Even if the use of regional climate models (RCMs) would allow for even higher resolution, RCMs do not provide global coverage or global consistency.…”
Section: Introductionmentioning
confidence: 99%
“…Another major outlook from this research is the potential benefit of employing GCMs with an eddy-rich ocean resolution, which can be obtained for nominal resolutions as low as 0.1°x0.1°2 7,28 . Unlike EP ocean grids, which only include mesoscale eddies with broader horizontal extents (100 km), eddy-rich ocean grids incorporate smaller-scale eddies (20 to 100 km), resulting in a significantly higher number of these mesoscale eddies and a better represented mean climate 17,27,28,29,37 . The use of an eddy-rich grid was notably shown to further improve most benefits and bias reductions seen in EP GCMs, notably in terms of SST mean biases 27 .…”
Section: Other Types Of Prominent Atmospheric Blockings Such As Summe...mentioning
confidence: 99%
“…At the surface, the horizontal distribution of heat driven by mesoscale eddies importantly contribute to sharp SST gradients, thus acting on the atmospheric boundary layer and higher atmosphere through variations in surface stability on momentum transfer, cloud cover and pressure gradients 26 . They have notably been shown to contribute significantly to the realism of air-sea interactions in GCMs, as well as large-scale oceanic features 27,28,29 .…”
mentioning
confidence: 99%
“…The spatial resolution of GCMs has commonly been 25-300 km (e.g. Demory et al 2020;Moreno-Chamarro et al 2022) while it has been around 12 km in the state-of-the-art RCM simulations for Europe, such as those of the EURO-CORDEX project (Jacob et al 2020). Recently, climate models have reached even finer grid spacings (Stevens et al 2019;Coppola et al 2020).…”
Section: Introductionmentioning
confidence: 99%